Individual Response Variation in the Effects of Weight Loss and Exercise on Insulin Sensitivity and Cardiometabolic Risk in Older Adults - Brennan, Andrea M.; Standley, Robert A.; Yi, Fanchao; Carnero, Elvis A.; Sparks, Lauren M.; Goodpaster, Bret H. (Frontiers in Endocrinology, 2020)
Weight loss induced by decreased energy intake (diet) or exercise generally has favorable effects on insulin sensitivity and cardiometabolic risk. The variation in these responses to diet-induced weight loss with or without exercise, particularly in older obese adults, is less clear. The objectives of our study were to (1) examine the effect of weight loss with or without exercise on the variability of responses in insulin sensitivity and cardiometabolic risk factors and (2) to explore whether baseline phenotypic characteristics are associated with response. Sedentary older obese (BMI 36.3 ± 5.0 kg/m2) adults (68.6 ± 4.7 years) were randomized to one of 3 groups: health education control (HED); diet-induced weight loss (WL); or weight loss and exercise (WL+EX) for 6 months. Composite Z-scores were calculated for changes in insulin sensitivity (C_IS: rate of glucose disposal/insulin at steady state during hyperinsulinemic euglycemic clamp, HOMA-IR, and HbA1C) and cardiometabolic risk (C_CMR: waist circumference, triglycerides, and fasting glucose). Baseline measures included body composition (MRI), cardiorespiratory fitness, in vivo mitochondrial function (ATPmax; P-MRS), and muscle fiber type. WL+EX groups had a greater proportion of High Responders in both C_IS and C_CMR compared to HED and WL only (all p<0.05). Pre-intervention measures of insulin (r=0.60) and HOMA-IR (r=0.56) were associated with change in insulin sensitivity (C_IS) in the WL group (p<0.05). Pre-intervention measures of glucose (r=0.55), triglycerides (r=0.53), and VLDL (r=0.53) were associated with change in cardiometabolic risk (C_CMR) in the WL group (p<0.05), whereas triglycerides (r=0.59) and VLDL (r=0.59) were associated with C_CMR (all p<0.05) in WL+EX. Thus, the addition of exercise to diet-induced weight loss increases the proportion of older obese adults who improve insulin sensitivity and cardiometabolic risk. Additionally, individuals with poorer metabolic status are more likely to experience greater improvements in cardiometabolic risk during weight loss with or without exercise.